Estudo de viabilidade de investimento em geração de energia elétrica em usinas de açúcar e álcool - Gregori Filho, Alessandro (2009)
The objective of this work is to analyze returns of investments in energy cogeneration plants from bagasse inside sugar cane mills, considering the regulation scenario of the Brazilian electric sector and the implementation costs of this type of project. The results should be able to demonstrate that this kind of investment is very profitable, pointing out the most important variables regarding the return on invested capital analyses. In order to accomplish this dissertation will be used some official information from Aneel releases, interview with sugar cane mill owners and specific bibliography. Moreover, for the valuation analyses techniques of free cash flow (FCF) and CAPM will be used, to determine the minimum return acceptable by the shareholders for this kind of project. Among the contributions of this dissertation the sensibility analyses can be pointed out in order to determine the most important variables that could be used by the Government in order to develop public policies more effective to stimulate this kind of investments'